Pengaruh Kreativitas, Modal Usaha Dan Minat Berwirausaha Mahasiswa Uin Raden Mas Said Surakarta Terhadap Ekonomi Kreatif - Anugerah Sekar Kharisma (Academica: Journal of Multidisciplinary Studies, 2024)
This study aims to determine how Gen Z students' creative interest, venture capital, and entrepreneurial interest impact their creative economy.To determine the relationship between two or more variables, this study used a quantitative approach. In this study, the population consists of Gen Z students who own businesses or are entrepreneurs.There are three independent variables used in this study including creativity, business capital, and entrepreneurial interest. The dependent variable of this study is the creative economy of Gen Z students. The study used T test, F test, R2 test, regression equation model estimation, validity, reliability, normality, heteroscedasticity, and autocorrelation to analyze the data. This research shows the results that there is a significant positive influence on the influence of creativity, business capital, and interest in entrepreneurship on the creative economy of Gen Z students.